Impact Behaviour of the Japanese Sword - DAIMARUYA, Masashi; KOBAYASHI, Hidetoshi (Engineering Transactions, 2012)
The Japanese sword is a weapon peculiar to Japan. The present study is concerned with the joint between tohshin (blade) and tsuka (hilt) of the Japanese sword. Only one mekugi- take (retaining peg made of bamboo) with about 5mm in diameter holds the tang in the hilt. However a slender mekugi might not be broken, even in the case of violent sword-fighting. This fact has been historically demonstrated in many battles by Japanese swords. In this study it is examined theoretically and experimentally from the viewpoint of impact engineering why a mekugi used in Tachi and Katana may not be broken. As a result, it is found that such a strong force as breaking a mekugi-take does not act on it, because of the location of mekugi- ana (a hole for mekugi ) in the tang, which has been made in the Japanese sword by following the traditional code of sword-smiths.